Applied Ethics in a Troubled World
XXI, 319 p.
Keywords: During the last two decades, applied ethics has not only developed into one of the most important philosophical disciplines but has also differentiated into so many subdisciplines that it is becoming increasingly difficult to survey it. A much-needed overview is provided by the eighteen contributions to this volume, in which internationally renowned experts deal with central questions of environmental ethics, bioethics and medical ethics, professional and business ethics, social, political, and legal ethics as well as with the aims and foundations of applied ethics in general. Thanks to a philosophical introduction and selected bibliographical references added to each chapter, the book is very well suited as a basis for courses in applied ethics. It is directed not only to philosophers and to ethicists from other disciplines but to scientists in general and to all people who are interested in the rational discussion of moral principles and their application to concrete problems in the sciences and in everyday life.